Penyalahgunaan Wewenang Sebagai Tindak Pidana Korupsi dalam Pengadaan Barang dan Jasa Pemerintah - Asmarani, Nur (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research aims to analyze, explain and understand the essence of government procurement of goods and services based on Presidential Decree Number 172 of 2014, the legal position of officials making commitments and law enforcement regarding abuse of authority in the procurement of goods and services. The type of research used is normative juridical, namely to examine legal concepts related to the procurement of government goods and services. This matter relates to the essence of procurement of goods and services based on Presidential Decree Number 172 of 2014, the legal position of officials making commitments and criminal responsibility for abuse of authority in the implementation of procurement of goods and services. The research results reveal that the procurement of goods and services is not only regulated by one regulation. This is because the procurement of goods and services is a long process, from the budget planning process, the budget management process, the process of procuring goods with a planned budget, and accountability for the results of the procurement of goods and services administratively and technically, as clearly regulated in Presidential Decree Number 172 of 2014. The legal position of the official making the commitment is as a government user of goods and services, who has taken legal action not only from a public aspect but also from a civil aspect. The abuse of authority by commitment-making officials is a criminal act of corruption that is detrimental to state finances and is completely contrary to the theory of the welfare state. A protective approach tends to create opportunities for KKN in the procurement of goods and services, so it needs to be avoided. Apart from that, law enforcement against abuse of authority in the procurement of goods and services is carried out firmly, without being selective about officials who make certain commitments.